Digital-twin for particle-laden viscoelastic fluids: ML-Based models to predict the drag coefficient of random arrays of spheres - Loiro, Carina Luzia Melo Monteiro (2021)
MIT-EXPL/TDI/0038/2019. FEDER funds through the COMPETE 2020 Programme and National Funds through FCT (Portuguese Foundation for Science and Technology) under the projects UIDB/05256/2020, UID-P/05256/2020, APROVA (MIT-EXPL/TDI/0038/2019) - Aprendizagem PROfunda na modelação de escoamentos com fluidos de matriz Viscoelástica Aditivados com partículas (POCI-01-0145-FEDER-016665) and HPC-EUROPA3 (INFRAIA-2016-1-730897). The authors would like to acknowledge the Minho University cluster under the project NORTE-07-0162-FEDER000086 (URL: http://search6.di.uminho.pt), the Minho Advanced Computing Center (MACCcpca_a2_6052_2020) (URL: https://macc.fccn.pt) and Julich Super Computing Centre (jusuf-iceiprace-2020-0009) for providing HPC resources that have contributed to the research results reported within this poster